A genome-wide cross-phenotype meta-analysis of the association of blood pressure with migraine - Yanjun Guo (Nature Portfolio, 2020)
The association between blood pressure (BP) and migraine is poorly understood. Here, the authors explore this relationship using summary-level GWAS data for BP and migraine. Cross-trait meta-analysis reveals shared loci between BP and migraine, while Mendelian randomization suggests that diastolic BP specifically plays a key role in migraine susceptibility.